2022
DOI: 10.3389/fmicb.2022.822304
|View full text |Cite
|
Sign up to set email alerts
|

Cas1 and Fen1 Display Equivalent Functions During Archaeal DNA Repair

Abstract: CRISPR-Cas constitutes an adaptive prokaryotic defence system against invasive nucleic acids like viruses and plasmids. Beyond their role in immunity, CRISPR-Cas systems have been shown to closely interact with components of cellular DNA repair pathways, either by regulating their expression or via direct protein-protein contact and enzymatic activity. The integrase Cas1 is usually involved in the adaptation phase of CRISPR-Cas immunity but an additional role in cellular DNA repair pathways has been proposed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Moreover, the contrast between the resistance of the Δcas3 mutant and the sensitivity of the Δcas genes mutant to DNA damaging agents, suggests that different cas genes might affect the susceptibility to DNA damage differently and in opposing directions in H. volcanii . Indeed, Cas1 contributes to DNA repair in E. coli (Babu et al 2011 ), has been recently shown to contribute to DNA repair in H. volcanii , and its deletion alongside the other cas genes could increase sensitivity to DNA damage (Wörtz et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the contrast between the resistance of the Δcas3 mutant and the sensitivity of the Δcas genes mutant to DNA damaging agents, suggests that different cas genes might affect the susceptibility to DNA damage differently and in opposing directions in H. volcanii . Indeed, Cas1 contributes to DNA repair in E. coli (Babu et al 2011 ), has been recently shown to contribute to DNA repair in H. volcanii , and its deletion alongside the other cas genes could increase sensitivity to DNA damage (Wörtz et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The three stages of the CRISPR-Cas immunity process (adaptation, maturation, and interference) have been well studied and characterized, and the function of the cas genes has been elucidated in several types and subtypes, including I-B systems, such as that of the haloarchaeon H. volcanii (Maier et al 2015 ). Recent work has shown that at least one protein, namely Cas1, also participates in DNA repair (Babu et al 2011 ; Wörtz et al 2022 ). However, the role of other cas genes in DNA repair is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MONSDA has been successfully applied to a variety of projects, including standard RNA-SEQ and DE analysis [37], Differential transcript usage analysis [38], custom tailored RNA-Seq approaches [29] and a series of projects under review or ongoing. We provide a companion repository https://github.com/jfallmann/MONSDA_companion which will host all configuration files used for analysis of published data and is open to be used as sharing platform all users.…”
Section: Resultsmentioning
confidence: 99%
“…Cas1 and Cas2 are responsible for acquiring new spacers and are the most conserved Cas proteins [ 7 ]. Cas1 exhibits nuclease activity against singe-stranded, double-stranded, and branched DNAs, including Holliday junctions, replication forks and 5′-flaps [ 8 , 9 , 10 ]. The Cas1-Cas2 integrase complex directly catalyses nucleophilic attack of the protospacer at the leader end of the CRISPR array [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%